Learning Malay folk song using M-learning model designed - Loo, Fung Ying; Loo, Fung Chiat (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
This research developed a M-learning model and approach with an attempt to bring forward an edutainment concept in generating interest in local folk songs. An M-learning music programme using Malay folk song was designed, focussing on the learning on rhythmic subdivision and tempo stability. The learning outcome among respondents who are adult beginner piano students was carried out in an experiment. The result shows that ability and interest to perform the designated set of rhythmic pattern was significantly higher using the M-learning model. In addition, the test shows that the model is a potential tool to develop awareness of traditional Malay folk song.